FORMULACIÓN DE UNA CREMA CORPORAL NATURAL A BASE DE CERA DE ABEJA, ACEITE DE AGUACATE (Persea americana) Y ACEITE ESENCIAL DE CLAVO DE OLOR (Eugenol - Mora Andrade, Rosario Lissbeth (2023)
It is known that the field of agribusiness is widely varied, and the object of its study is the transformation of raw materials of plant and animal origin into processed food, non-food, and input products, through process management. Wanting to focus on the production of a non-food product, the object of this study was the formulation of a natural body cream based on beeswax, avocado oil (Persea Americana) and clove essential oil (Eugenol). To prepare the product, first the refined wax and the essential oil of clove were obtained to formulate the emulsion.